2004
DOI: 10.1002/eji.200324514
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bonds in merozoite surface protein 1 of the malaria parasite impede efficient antigen processing and affect the in vivo antibody response

Abstract: The 19 kDa C‐terminal fragment of the malaria parasite merozoite surface protein 1 (MSP119) is a leading malaria vaccine candidate. In rodents, high antibody levels to this protein confer protective immunity, and can be generated by immunization with the antigen in adjuvants. In natural human infections, however, MSP119‐specific antibody responses can be short‐lived andcomparatively low, despite repeated exposure to infection. The tightly folded structure of MSP119 is stabilized by five or six disulfide bonds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…1c). In agreement with these data, MSP-1 19 is known to be refractory to antigen processing 8 , and the CD4 + T helper cell response against MSP-1 33 is likely to be crucial for antibody responses to MSP-1 19 .…”
supporting
confidence: 71%
“…1c). In agreement with these data, MSP-1 19 is known to be refractory to antigen processing 8 , and the CD4 + T helper cell response against MSP-1 33 is likely to be crucial for antibody responses to MSP-1 19 .…”
supporting
confidence: 71%
“…MSP-1 19 is known to be poorly immunogenic, eliciting low levels of antibodies and poor T-cell activation and functional T helper cells in humans (29,31). A number of studies have shown that the addition or presence of exogenous helper T-cell epitopes provides help to B cells, thereby enhancing the immunogenicity of PfMSP-1 19 (32).…”
Section: Discussionmentioning
confidence: 99%
“…No host cell protein contamination was observed in purified PfMSP-Fu 24 , as determined by an ELISA (0.3 ng/ml [0.03%]) and by Western blotting (data not shown). The protective immune responses induced by PfMSP-1 19 have been shown to be dependent on protein conformation (31). We tested the conformational integrity of the PfMSP-1 19 component in PfMSP-Fu 24 by two conformation-sensitive MAbs, 1H4 and 2E10 (42).…”
Section: Expression Purification and Characterization Of Pfmsp-fu 24mentioning
confidence: 99%
See 1 more Smart Citation
“…The immunogen, designed based on the primary structure of protein which is directly or indirectly responsible for the conformation and/or accessibility of MAb epitopes, may be modified following expression in mammalian cells. (13)(14)(15)(16) Although the mechanism of this modification is unknown, at least two possibilities exist: re-arrangement of disulfide bonds (17) and phosphorylation. (18,19) ECRG2 belongs to the kazal family which contains the conservative pattern x(8)-C-x(6)-C-x(7)-C-x(6)-Yx(3)-C-x(2,3)-C-x(17)-C, and these conservative cysteines are involved in three disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%